The Impact of Organizational, Occupational, and Individual Factors Nurses’ compliance in Practicing Hand Hygiene - Paramitha Kusuma Wardhani; Andreas Nugroho Susanto; Ratna Dwi Wulandari (Universitas Aisyah Pringsewu, 2023)
Hospitals and other healthcare facilities place a high priority on hand hygiene because pathogen-contaminated hands can spread infectious diseases known as healthcare-associated infections (HAIs). According to the findings of preliminary research that involved document tracing, the implementation of hand hygiene at private hospitals in Manado from January to July 2020 did not meet the stated standards for compliance indicators. This study aimed to analyze the influence of organizational, occupational, and individual factors on the level of compliance of nurses in Private Hospitals in Manado in performing hand hygiene practices. This study was an analytical observational study using a cross-sectional design. Data was collected using questionnaires and observations of 125 respondents from 14 treatment rooms at Private Hospital in Manado. Multiple linear regression was performed to analyze the data. The results of the multiple linear regression test showed that climate factors of safety, facility availability, information and training, supervision, and risk perception (p-value: 0.001; 0.017; 0.002; 0.019; and 0.022) were significant for nurses’ compliance in performing hand hygiene. The hospital management is expected to provide inspiration to increase nurse motivation, build communication-related to hand hygiene practices, and implement reward and punishment programs. Abstrak: Hand hygiene merupakan praktek yang penting di rumah sakit maupun fasilitas pelayanan kesehatan lainnya karena. tangan yang terkontaminasi patogen dapat menularkan penyakit infeksi yang disebut Healthcare-associated infections (HAIs). Hasil studi pendahuluan berupa telusur dokumen ditemukan bahwa capaian indikator kepatuhan pelaksanaan hand hygiene di RS Privat di Manado selama Januari hingga Juli 2020 belum mencapai standar yang telah ditetapkan. Penelitian ini bertujuan melakukan menganalisis pengaruh faktor organisasi, pekerjaan, dan individu terhadap tingkat kepatuhan perawat di RS Privat di Manado dalam melaksanakan praktek hand hygiene. Penelitian ini merupakan penelitian observasional analitik menggunakan desain cross-sectional. Pengumpulan data dilakukan melalui pengisian kuisioner dan observasi terhadap 125 responden dari 14 ruang perawatan di RS Privat di Manado. Analisis data dilakukan dengan uji regresi linear ganda. Hasil uji regresi linear ganda menunjukkan bahwa faktor iklim keselamatan, ketersediaan fasilitas, informasi dan pelatihan, supervisi, dan persepsi risiko (p-value: 0.001; 0.017; 0.002; 0.019; dan 0.022) signifikan terhadap kepatuhan perawat dalam melakukan hand hygiene. Pihak manajemen rumah sakit diharapkan dapat memberikan inspirasi untuk meningkatkan motivasi perawat dan membangun komunikasi terkait praktek hand hygiene, serta menerapkan program reward and punishment.